Communication: spaces and collective memories. Case study - Pardo Abril, Neyla Graciela (2022)
In the current socio-political situation in Colombia and in the post-agreement scenario (2016), in coexistence with the internal armed conflict, the relationship between memory and space is reflected; it is formulated from its communicative and political character, taking into account, as a starting point, that memory is a social construction, anchored in space-time in the daily life of communities, formulated as a subjective interaction, which, when socialized, becomes collectivized; that is, it has an intersubjective nature, managing dialogic and social networks, updating ways of knowing reality and influencing the transformations of communities.   The objective is to formulate a reflection on the socio-discursive and political-cultural construction of memory, to address space-time in a place of memory in Bogotá; relationship that is characterized by having a communicative, symbolic and political dimension. In a first point, the relationship between memory and socio-communicative practices with the processes of construction of meaning is addressed. Second, the memory-space-place relationship in the national territory is explored, and how it serves as an anchor for the memory of the Colombian armed conflict, whose temporality exceeds six decades. In this process of design, production and socialization, the symbolic-discursive dimension is installed. Finally, in the third point, the Peace and Reconciliation Memory Center of the Capital District-Bogotá is analyzed semiotic-discursively, as part of the symbolic-public landscape, whose material and actional concretion is the sense of multiculturalism, social and political heterogeneity.